Stochastic simulation of mould growth performance of wood-frame building envelopes under climate change: risk assessment and error estimation - Wang, Lin; Defo, Maurice; Xiao, Zhe; Ge, Hua; Lacasse, Michael A (Buildings (Basel), 2021)
NRC publication: Yes